Oxigenioterapia hiperbárica altera positivamente a disfunção orgânica de cadelas em sepse por HEC-P - Schiefler, Otávio Henrique de Melo (2023)
The incidence of cystic-pyometra endometrial hyperplasia (HEC-P) in dogs is high, being considered the main genitourinary surgical disease in the species. Commonly this alteration is accompanied by sepsis or septic shock and, if not properly treated or stabilized, the low oxygen demand to the tissues causes the animal to develop organic dysfunction preceded by multiple organ failure. Hyperbaric oxygen therapy is a treatment modality on the rise in veterinary medicine, with positive results in experimental models in the resolution of sepsis. The objective of this work was to use hyperbaric oxygen therapy as adjuvant therapy in septic dogswithHEC-P presenting at least one organic dysfunction according to the SOFA score criteria. For this, eight animals were included in the study, four of which were submittedto hyperbaric sessions with 2 ATA, during 75 minutes, over three sessions, with an interval of 24 hours between each session. Serial SOFA scores and central venous saturation (SvcO 2) scores were used as parameters for evaluation and monitoring of the effects of hyperbaric oxygen therapy. Eight animals were divided into two groups, four animals submitted to HBOT and four animals in the control group. In both groups, four evaluations were performed: D0 (preoperative), D1 (24 hours postoperatively), D2 (48 hours postoperatively) and D3 (72 hours postoperatively). The results showed a significant difference between the control and HBOT groups in times D0 (p=0.014), D1 (p=0.014) and F2 (p=0.042), but there was no statistical difference in D3 (p=0.10) in the SOFA parameters. However, the HBOT group had a 51% reduction in admission values (D0) after three sessions of hyperbaric therapy while the control group reduced the initial SOFA values by 29%. There was no significant difference between the groups in the same time interval, nor between the same group at the different times analyzed. We concluded that hyperbaric oxygen therapy at 2 ATA for 75 minutes for three sessions obtained a positive result in reducing the organic dysfunction of dogs in hec-p sepsis, but did not interfere in the values of SvcO2.